Food plant sanitation design, maintenance, and good manufacturing practices - Cramer, Michael M. (Taylor & Francis, 2013)
"Completely revised and updated, this book shows how to effectively remove soil and microorganisms from the processing environment to prevent unhygienic manufacturing conditions. The book discusses the regulatory requirements of food plant sanitation and the identification of microorganisms of food manufacturing concern. It explores the principles of sanitary design, the use of proven sanitation techniques, and the means of verifying sanitation, such as adenosine triphosphate (ATP). The final chapters identify sanitary practices for plant personnel and visitors, provide a comprehensive pest management plan, and offer strategies for preventing chemical and physical food safety hazards"-- Provided by publisher.
Keywords: Food industry and trade -- Sanitation.; elektronické knihy; electronic books